Animal manure : recycling, treatment, and management - Sommer, Sven Gjedde, 1955-; Jensen, Lars Stoumann; Christensen, Morten L.; Schmidt, Thomas (Technology Transfer Professional) (Chichester, West Sussex : John Wiley & Sons, Inc., 2013)
A rapidly changing and expanding livestock and poultry production sector is causing a range of environmental problems on local, regional and global scales. Animal Manure Recycling: Treatment and Management presents an accessible overview of environmentally friendly technologies for managing animal manure more efficiently and in a sustainable manner. This book describes the physical and chemical characteristics of animal manure and microbial processes, featuring detailed examples and case studies showing how this knowledge can be used in practice. Readers are introduced to the sus.
6.2.2 Expression of Pathogen Reduction6.3 Manure Treatment Alternatives; 6.3.1 Storage; 6.3.2 Anaerobic Treatment; 6.3.3 Composting; 6.4 Chemical Treatment; 6.4.1 Ammonia Treatment; 6.4.2 Ammonia Sanitisation at the Farm Level; 6.5 Summary; References; 7 Solid-Liquid Separation of Animal Slurry; 7.1 Introduction; 7.2 Removal and Separation Efficiency; 7.3 In-House Separation; 7.4 Solid-Liquid Separation of Manure Slurry; 7.4.1 Sedimentation; 7.4.2 Centrifugation; 7.4.3 Drainage; 7.4.4 Filtration with Pressure; 7.4.5 User Demand on Performance of the Technology.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Animal waste -- Recycling; Biomass energy; Farm manure; Manures; Animal waste -- Recycling; TECHNOLOGY & ENGINEERING -- Environmental -- General; Animal waste -- Recycling; Biomass energy; Farm manure; Manures; Electronic books; Electronic books; Electronic books